2013
DOI: 10.1057/jit.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

The Ongoing Quest for the it Artifact: Looking Back, Moving Forward

Abstract: More than 10 years ago, Orlikowski and Iacono (2001) examined the conceptualization of Information Technology (IT) in Information Systems Research (ISR) articles published in the 1990s. Their main conclusion was that the majority of these articles did not properly conceptualize the IT artifact. They recommended that IS researchers start to theorize about the IT artifact and employ rich conceptualizations of IT. The Orlikowski and Iacono paper provides a strong anchor point from which to analyze the evolution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 58 publications
3
35
0
Order By: Relevance
“…This paper responds to the need to better define the IT artifact. For some, servicing this need means ‘incorporating more comprehensive and multi‐faceted conceptualizations of the IT artifact’ (Akhlaghpour et al ., , p. 151). For others, broadening the meaning of the concept (IT artifact) creates confusion.…”
Section: Introductionmentioning
confidence: 97%
“…This paper responds to the need to better define the IT artifact. For some, servicing this need means ‘incorporating more comprehensive and multi‐faceted conceptualizations of the IT artifact’ (Akhlaghpour et al ., , p. 151). For others, broadening the meaning of the concept (IT artifact) creates confusion.…”
Section: Introductionmentioning
confidence: 97%
“…It has been more than a decade since Orlikowski and Lacono [48] found that most of the published studies in the IS field tended to overlook the conceptual significance of the IT artifact by using too simplistic measures, disconnecting it from social settings, black-boxing it, or even excluding it entirely. Recent reviews of the IT artifact's role propose that the field did not witness much improvement [69]. Our research was intended to shed light on the cloud ecosystem artifact in order to gain insights into the fit of cloud sourcing arrangements.…”
Section: Resultsmentioning
confidence: 99%
“…Answers to these questions on the philosophy of information (Floridi, 2002(Floridi, , 2011 and technology (Feenberg, 1991(Feenberg, , 2010bIhde, 1990Ihde, , 1993 are being provided by scholars outside of IS. The ongoing struggle to define the IT artefact (Akhlaghpour, Wu, Lapointe, & Pinsonneault, 2013;Alter, 2015;Orlikowski & Iacono, 2001) is, in fact, a struggle that metaphysics offers several opportunities, despite the dearth of such studies in IS.…”
Section: Philosophical Interventions In the Is Discoursementioning
confidence: 99%